Evaluating the Non-conventional Achalasia Treatment Modalities - Tustumi, Francisco (Frontiers in Medicine, 2022)
Introduction: Achalasia is a primary esophageal dysmotility disorder. Despite the high volume of studies addressing the conventional treatments for achalasia, few are debated regarding the non-conventional treatments, such as cardiectomy, cardioplasty, endoluminal substances injection (ethanolamine oleate, polidocanol, botulinum toxin), stents, and certain drugs (beta-agonists, anticholinergic, nitrates, calcium channel blockers, and phosphodiesterase inhibitors). Methods: A critical review was performed. Results: Endoscopic, surgical, and pharmacological treatments were included. A qualitative synthesis was presented. Conclusion: Non-conventional therapeutic options for treating achalasia encompass medical, endoscopic, and surgical procedures. Clinicians and patients need to know all the tools for the management of achalasia. However, several currently available studies of non-conventional treatments lack high-quality evidence, and future randomized trials are still needed.